Molecular characterization of a new SARS-CoV-2 recombinant cluster XAG identified in Brazil - Silva, Thaís de Souza; Salvato, Richard Steiner; Gregianini, Tatiana Schäffer; Gomes, Ighor Arantes; Pereira, Elisa Cavalcante; de Oliveira, Eneida; de Menezes, André Luiz; Barcellos, Regina Bones; Godinho, Fernanda Marques; Riediger, Irina; Debur, Maria do Carmo; de Oliveira, Cristina Mendes; et al. (Frontiers in Medicine, 2022)
Recombination events have been described in the Coronaviridae family. Since the beginning of the SARS-CoV-2 pandemic, a variable degree of selection pressure has acted upon the virus, generating new strains with increased fitness in terms of viral transmission and antibody scape. Most of the SC2 variants of concern detected so far carry a combination of key amino acid changes and indels. However, recombination may also reshuffle existing genetic profiles of distinct strains, potentially giving origin to recombinant strains with altered phenotypes. However, co-infection and recombination events are challenging to detect and require in-depth curation. Here, we present the molecular characterization of a new SARS-CoV-2 recombinant between BA.1.1 and BA.2.23 Omicron lineages identified in Brazil. We characterized four mutations that had not been previously described in any of the recombinants already identified worldwide and described the likely breaking points. Moreover, through phylogenetic analysis, we showed that the newly named XAG lineage groups in a highly supported monophyletic group confirmed its evolutionary history from parental Omicron lineages and other recombinants already described. These observations were only possible thanks to the joint effort of bioinformatics tools auxiliary in genomic surveillance and the manual curation of experienced personnel, demonstrating the importance of genetic and bioinformatic knowledge in genomics.